Efficacy and Safety of, and Patient Satisfaction with, Colonoscopic-Administered Fecal Microbiota Transplantation in Relapsing and Refractory Community- and Hospital-Acquired Clostridium difficile Infection. Issue 8 (2014) - Khan, Muhammad Ali; Sofi, Aijaz Ahmed; Ahmad, Usman; Alaradi, Osama; Khan, Abdur Rahman; Hammad, Tariq; Pratt, Jennifer; Sodeman, Thomas; Sodeman, William; Kamal, Sehrish; Nawras, Ali
Abstract : OBJECTIVE: To report the efficacy and safety of, and patient satisfaction with, colonoscopic fecal microbiota transplantation (FMT) for community- and hospital-acquired Clostridium difficile infection (CDI). METHODS: A retrospective medical records review of patients who underwent FMT between July 1, 2012 and August 31, 2013 was conducted. A total of 22 FMTs were performed on 20 patients via colonoscopy. The patients were divided into 'community-acquired' and 'hospital-acquired' CDI. Telephone surveys were conducted to determine procedure outcome and patient satisfaction. Primary cure rate was defined as resolution of diarrhea without recurrence within three months of FMT, whereas secondary cure rate described patients who experienced resolution of diarrhea and return of normal bowel function after a second course of FMT. RESULTS: Nine patients met the criteria for community-acquired CDI whereas 11 were categorized as hospital-acquired CDI. A female predominance in the community-acquired group (88.89% [eight of nine]) was found (P=0.048). The primary cure rate was 100% (nine of nine) and 81.8% (nine of 11 patients) in community- and hospital-acquired CDI groups, respectively (P=0.189). Two patients in the hospital-acquired group had to undergo a repeat FMT for persistent symptomatic infection; the secondary cure rate was 100%. During the six-month follow-up, all patients were extremely satisfied with the procedure and no complications or adverse events were reported. CONCLUSION: FMT was a highly successful and very acceptable treatment modality for treating both community- and hospital-acquired CDI.